Dopamine D 4 receptor, but not the ADHD-associated D 4.7 variant, forms functional heteromers with the dopamine D 2S receptor in the brain - González, S. (2012)
Polymorphic variants of the dopamine D 4 receptor have been consistently associated with attention-deficit hyperactivity disorder (ADHD). However, the functional significance of the risk polymorphism (variable number of tandem repeats in exon 3) is still unclear. Here, we show that whereas the most frequent 4-repeat (D 4.4) and the 2-repeat (D 4.2) variants form functional heteromers with the short isoform of the dopamine D 2 receptor (D 2S), the 7-repeat risk allele (D 4.7) does not. D 2 receptor activation in the D 2S-D 4 receptor heteromer potentiates D 4 receptor-mediated MAPK signaling in transfected cells and in the striatum, which did not occur in cells expressing D 4.7 or in the striatum of knockin mutant mice carrying the 7 repeats of the human D 4.7 in the third intracellular loop of the D 4 receptor. In the striatum, D 4 receptors are localized in corticostriatal glutamatergic terminals, where they selectively modulate glutamatergic neurotransmission by interacting with D 2S receptors. This interaction shows the same qualitative characteristics than the D 2S-D 4 receptor heteromer-mediated mitogen-activated protein kinase (MAPK) signaling and D 2S receptor activation potentiates D 4 receptor-mediated inhibition of striatal glutamate release. It is therefore postulated that dysfunctional D 2S-D 4.7 heteromers may impair presynaptic dopaminergic control of corticostriatal glutamatergic neurotransmission and explain functional deficits associated with ADHD.